Transitional Justice and Women’s Rights: Possibilities and challenges - Mantilla Falcón, Julissa (2015)
This article is about the issue of Transitional Justice and its relationship with women’s rights. The author defines the concept of this term and makes a list of the rights that are covered by it, also she mentions that women have not been properly considered in the Transitional Justice process by not having the gender perspective, which is necessary to be done. The author concludes by stating that the reports have been more truthful when gender perspective was applied.